Postoperative multimodal pain management: a narrative review of current practices, clinical and educational gaps, and future directions - Lopez, Braden M.; Lee, Brent M.; Miller, Michael D.; Ibrahim, Mohab M.; Vanderah, Todd W.; Riegel, Arthur C. (Frontiers in Anesthesiology, 2025)
Pain is among the most commonly reported side effects following surgical interventions; however, its management remains a significant challenge due to its multifaceted nature, with studies indicating that up to 80% of surgical patients experience inadequate pain control. Although multimodal pain management (MMPM) is widely recommended as a tool to help mitigate the ongoing opioid epidemic, a universally standardized approach for pain management is lacking and highly dependent on individual clinician practices. Pain perception is inherently subjective, and while objective measurement tools are emerging, self-reported pain scales continue to dominate clinical practice. Differences in pain perception, further complicate efforts to standardize care, demonstrating the need for personalized approaches. Notably, there is a deficiency in surgical education regarding formalized training in postoperative pain management, which leaves medical students and residents without a concrete foundation in evidence-based pain management strategies. This narrative review explores the pathophysiology of pain, evaluates current recommendations in surgery, and emphasizes preoperative optimization. It also argues for, and underscores the necessity for, comprehensive and structured pain management education across all surgical specialties. Furthermore, the review identifies future directions, particularly in pain prediction and the development of surgical guidelines that can facilitate a comprehensive pain management framework while accommodating patient-specific modifications.